Falls prevention in elderly adults :go beyond (2018)
Falls in older adults are the second cause of hospitalization in the world and can cause different injuries causing health problems such as disability andeven death. The most common injury is a hip fracture. The World Health Organization estimates that by the year 2050, between 7 and 21 million hip replacements will be produced in Latin America. By having this information, it was decided to create a device with the aim of preventing and reducing hip injuries in elderly people. The device we created consists of a belt that has incorporated air pockets that open at the time of the fall, with the help of some oxygen bullets and an electrical system. This is how to prevent hip injuries. Similarly, improve the lifestyle in this population group